Non-contact infrared assessment of human body temperature: The journal Temperature toolbox. Issue 4 (2nd October 2021) - Foster, Josh; Lloyd, Alex Bruce; Havenith, George
ABSTRACT: The assessment of human internal/core temperature ( T core ) is relevant in many scientific disciplines, but also for public health authorities when attempting to identify individuals with fever. Direct assessment of T core is often invasive, impractical on a large scale, and typically requires close contact between the observer and the target subject. Non-contact infrared thermometry (NCIT) represents a practical solution in which T core can potentially be assessed from a safe distance and in mass screening scenarios, by measuring skin temperature at specific anatomical locations. However, the COVID-19 pandemic has clearly demonstrated that these devices are not being used correctly, despite expert guided specifications available in International Standard Organization (ISO) documents. In this review, we provide an overview of the most pertinent factors that should be considered by users of NCIT. This includes the most pertinent methodological and physiological factors, as well as an overview on the ability of NCIT to track human T core . For practical use, we provide a checklist based on relevant ISO standards which are simple to follow and should be consulted prior to using NCIT for assessment of human T core . Our intention is for users of NCIT to adopt this checklist, which may improve the performance of NCIT for its ability to track T core .